Analysis Of Not Rotating Valve Rotator On Main Engine Performance In KM. LABOBAR - Dewantoro, Pamungkas Ade; Narto, Amad; Utari, Riyadini (LPPM AKMI SUAKA BAHARI CIREBON, 2024)
The main engine serves as the primary power source for propelling the ship forward and backward. This engine operates on an internal combustion system, where fuel and air are compressed in the combustion chamber to generate thermal energy, which is then converted into mechanical energy through piston movement. This study employs a qualitative descriptive method with SHEL data analysis techniques, identifying the causative factors, impacts, and corrective measures associated with the non-rotation of the valve rotator in the main engine. The findings indicate that the primary cause of the valve rotator's non-rotation is improper installation of the valve collet and wear on the valve rotator body, which affects valve performance and reduces the overall efficiency of the main engine. Corrective actions include replacing the valve rotator and performing routine lubrication checks to prevent further damage.